Novel Method for Floating Synthesizing Heavy Metal Particles as Flowing Anode of Zinc-Air Fuel Cell - Chen Yang Wu; Kuohsiu David Huang; Horng Yi Tang (Advances in Materials Science and Engineering)
In this study, centrally hollow microspheres of zinc were synthesized. The microspheres were then mixed with KOH electrolyte to form zinc sol, which was coagulated and precipitated. Afterward, we employed a novel technique to enable the permanent floating of zinc particles, which involved stirring zinc sol with air using a magnetic stirrer. This resulted in the formation of foam in which the zinc particles permanently floated. We then added 65 wt% of the electrolyte (KOH) to prepare 35 wt% of zinc sol. We tested the cell and found the values of current density, specific energy, and electric capacity to be 7.41 mA/cm2, 840.14 Wh/kg, and 3023 mAh, respectively.